SURGICAL SIGNIFICANCE OF ANATOMICAL VARIATIONS OF THE PARATHYROID GLANDS - Milic, Ljiljana; Cuk, Vladica; Juloski, Jovan; Tomic, Ratomir; Surlan, Marko; Starcevic, Ana (Medical Research, 2025)
A solid understanding of the surgical anatomy of the parathyroid glands is based on a thorough knowledge of their embryonic development. Anatomical variations in the number, morphology, vascularization, and localization of the parathyroid glands present a challenge during surgical exploration of the neck, both in the treatment of hyperparathyroidism (HPT) and in thyroid surgery. In about 2.3% of patients undergoing thyroidectomy, incidental parathyroidectomy occurs. Our review aims to highlight the incidence of anatomical variations in the localization, number, morphology, and vascularization of the parathyroid glands, as well as their significance in the surgical treatment of parathyroid gland functional disorders. A good understanding of embryologic development and neck anatomy is essential for parathyroid surgery. Contemporary imaging diagnostic modalities used in parathyroid surgery do not have the same sensitivity and specificity as in other surgical fields, and they significantly increase treatment costs. The success of surgical treatment largely depends on the surgeon's knowledge and experience.If parathyroid glands are not found in their usual locations, an extensive bilateral neck exploration must be performed. Meanwhile, parathyroid adenomas located in the mediastinum below the aortic arch require a specialized diagnostic and surgical approach. Measurement of intraoperative PTH (ioPTH) levels increases the success rate of surgical interventions.
Keywords: parathyroid glands, PTH, Anatomical variations.